Retinal pigment epithelium defects accelerate photoreceptor degeneration in cell type-specific knockout mouse models of choroideremia - Tolmachova, Tanya (2017)
PURPOSE. Choroideremia (CHM) is a progressive X-linked degeneration of three ocular layers (photoreceptors, retinal pigment epithelium, and choroid), with a complex and still largely unclear pathogenesis. To investigate the pathophysiology of CHM, the authors engineered mice with a cell type-specific Chm/Rep1 knockout (KO). METHODS. A mouse line carrying a conditional allele ChmFlox was crossed with the transgenic line IRBP-Cre to achieve Chm KO, specifically in the photoreceptor layer, and Tyr-Cre to produce Chm KO, specifically in the retinal pigment epithelial and other pigmented cells. ChmFlox, Tyr-Cre+ and ChmFlox, IRBP-Cre+ mice were mated to produce mice with Chm KO in both layers. All mouse lines were studied by histology, electron microscopy, electroretinography (ERG), scanning laser ophthalmoscopy (SLO), and biochemical methods. RESULTS. In ChmFlox, IRBP-Cre+ mice the authors observed the progressive degeneration of photoreceptors in the presence of normal retinal pigment epithelium (RPE). ChmFlox, Tyr-Cre+ mice exhibited coat color dilution and pigment abnormalities of the RPE in the presence of an intact outer nuclear layer. In 6- to 8-month-old ChmFlox, Tyr-Cre+, IRBP-Cre+ mice, the degeneration of photoreceptors was accelerated compared with ChmFlox, IRBP-Cre+ mice but became leveled with age, such that it was comparable at 12 to 14 months. Detailed ERG and SLO analysis supported the histopathologic findings. CONCLUSIONS. Defects in photoreceptors and RPE can arise because of intrinsic defects caused cell autonomously by the Chm KO. However, when both photoreceptors and RPE are diseased, the dynamics of the degenerative process are altered. Photoreceptor functional deficit and cell death manifest much earlier, suggesting that the diseased RPE accelerates photoreceptor degeneration.